Provisioning the Ottoman Capital: Istanbul’s market gardens between the seventeenth and nineteenth centuries - Akdal, Ayşe Nur. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2016., 2016)
This study is about market gardens and their gardeners, which were a distinc-tive part of Ottoman Istanbul until recently. It draws on first and second-hand sources to examine the locations, physical features, and property structures of market gardens together with those who worked in there and how they were organized. Moreover, the study reveals the role and importance of market gar-dens in the provisioning of the city. Based on archival material, the study describes the urban fabric, the labor structure, and migration with help of visual data. Although the market gar-dens of Istanbul played an important role in the provisioning of the city, shaped its urban landscape, and provided job opportunities for migrant labor-ers, they have not received the attention they deserve in Ottoman studies. e foremost goal of the study is to comprehensively document and compile the rich multi-faceted historical data. Another aim is to test two assumptions in the literature on Ottoman history against the historical data, namely, that Is-tanbul was a “city of consumption,” and that there was essentially a fixed, ethno-religious division of labor in the Empire.
Keywords: Gardens, Turkish -- Turkey -- Istanbul.